Hubungan Pengetahuan Dan Sikap Remaja Dengan Kecemasan Menghadapi Menarche Pada Siswi Kelas VII di SMP Katolik Makale Kecamatan Makale Tana Toraja - Hayuti Windha Pagiu; Fera Dwiyanti; Hermin Neli; Rosmita Jelni Tandigau (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Adolescence is a period of transition between childhood and adulthood which begins at the time of sexual maturity, namely between the ages of 11 or 12 to 20 years. Adolescence and menstruation are very closely related because menstruation is one of the important problems for teenage girls. This study aims to determine the relationship between the level of knowledge and attitudes of adolescents with anxiety about facing menarche in class VII students at Makale Tana Toraja Catholic Middle School. The research design used is descriptive analytic. Using the Cross Sectional method. With a total of 29 samples using proportional stratified random sampling technique. The analysis method was carried out using univariate and bivariate analysis methods using the Chi-square statistical test with a significance level of p-value <0.005. Research shows that there is no relationship between knowledge and anxiety about facing menarche with a p-value꞊0.668>0.05 and there is no relationship between attitudes and anxiety about facing menarche with a p-value꞊0.207>0.05. It can be concluded that there is no relationship between teenagers' knowledge and attitudes and anxiety about facing menarche at Makale Tana Toraja Catholic Middle School. The suggestion in this research is that it is hoped that teachers, especially BK (Guidance Counseling) teachers, should further improve the provision of information and guidance to their students regarding healthy behavior in dealing with menstruation and menstrual disorders.